Morphine Use in the ED and Outcomes of Patients With Acute Heart Failure: A Propensity Score-Matching Analysis Based on the EAHFE Registry - Miró, Òscar; Gil, Víctor; Martín-Sánchez, Francisco J; Herrero-Puente, Pablo; Jacob, Javier; Mebazaa, Alexandre; Harjola, Veli-Pekka; Ríos, José; Hollander, Judd E; Peacock, W Frank; Llorens, Pere (Chest, 2017)
The objective was to determine the relationship between short-term mortality and intravenous morphine use in ED patients who received a diagnosis of acute heart failure (AHF). Consecutive patients with AHF presenting to 34 Spanish EDs from 2011 to 2014 were eligible for inclusion. The subjects were divided into those with (M) or without IV morphine treatment (WOM) groups during ED stay. The primary outcome was 30-day all-cause mortality, and secondary outcomes were mortality at different intermediate time points, in-hospital mortality, and length of hospital stay. We generated a propensity score to match the M and WOM groups that were 1:1 according to 46 different epidemiological, baseline, clinical, and therapeutic factors. We investigated independent risk factors for 30-day mortality in patients receiving morphine. We included 6,516 patients (mean age, 81 [SD, 10] years; 56% women): 416 (6.4%) in the M and 6,100 (93.6%) in the WOM group. Overall, 635 (9.7%; M, 26.7%; WOM, 8.6%) died by day 30. After propensity score matching, 275 paired patients constituted each group. Patients receiving morphine had a higher 30-day mortality (55 [20.0%] vs 35 [12.7%] deaths; hazard ratio, 1.66; 95% CI, 1.09-2.54; P = .017). In patients receiving morphine, death was directly related to glycemia (P = .013) and inversely related to the baseline Barthel index and systolic BP (P = .021) at ED arrival (P = .021). Mortality was increased at every intermediate time point, although the greatest risk was at the shortest time (at 3 days: 22 [8.0%] vs 7 [2.5%] deaths; OR, 3.33; 95% CI, 1.40-7.93; P = .014). In-hospital mortality did not increase (39 [14.2%] vs 26 [9.1%] deaths; OR, 1.65; 95% CI, 0.97-2.82; P = .083) and LOS did not differ between groups (median [interquartile range] in M, 8 [7]; WOM, 8 [6]; P = .79). This propensity score-matched analysis suggests that the use of IV morphine in AHF could be associated with increased 30-day mortality.